Randomized controlled trial of an Internet delivered family cognitive behavioral therapy intervention for children and adolescents with chronic pain - Palermo, Tonya M. (2009)
Cognitive-behavioral therapy (CBT) interventions show promise for decreasing chronic pain in youth. However, the availability of CBT is limited by many factors including distance to major treatment centers and expense. This study evaluates a more accessible treatment approach for chronic pediatric pain using an Internet-delivered family CBT intervention. Participants included 48 children, ages 11–17 years, with chronic headache, abdominal, or musculoskeletal pain and associated functional disability, and their parents. Children were randomly assigned to a wait-list control group or an Internet treatment group. Primary treatment outcomes were pain intensity ratings (0–10 NRS) and activity limitations on the Child Activity Limitations Interview, both completed via an online daily diary. In addition to their medical care, the Internet treatment group completed 8 weeks of online modules including relaxation training, cognitive strategies, parent operant techniques, communication strategies, and sleep and activity interventions. Youth randomized to the wait-list control group continued with current medical care only. Findings demonstrated significantly greater reduction in activity limitations and pain intensity at post-treatment for the Internet treatment group and these effects were maintained at three-month follow-up. Rate of clinically significant improvement in pain was also greater for the Internet treatment group in comparison to the wait-list control group. There were no significant group differences in parental protectiveness or child depressive symptoms post-treatment. Internet treatment was rated as acceptable by all children and parents. Findings support the efficacy and acceptability of Internet delivery of family CBT for reducing pain and improving function among children and adolescents with chronic pain.